Libby loves science - Derting, Kimberly; Johannes, Shelli R. (Greenwillow Books, an imprint of HarperCollins Publishers, 2020)
Libby and her friends volunteer to run the science booth at their school fair and have some great ideas, but Libby does not always follow directions precisely. Includes a worksheet for each experiment mentioned.